-3(1+4n)=2n+3(-6n-1)

Simple and best practice solution for -3(1+4n)=2n+3(-6n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(1+4n)=2n+3(-6n-1) equation:



-3(1+4n)=2n+3(-6n-1)
We move all terms to the left:
-3(1+4n)-(2n+3(-6n-1))=0
We add all the numbers together, and all the variables
-3(4n+1)-(2n+3(-6n-1))=0
We multiply parentheses
-12n-(2n+3(-6n-1))-3=0
We calculate terms in parentheses: -(2n+3(-6n-1)), so:
2n+3(-6n-1)
We multiply parentheses
2n-18n-3
We add all the numbers together, and all the variables
-16n-3
Back to the equation:
-(-16n-3)
We get rid of parentheses
-12n+16n+3-3=0
We add all the numbers together, and all the variables
4n=0
n=0/4
n=0

See similar equations:

| 8=8-t | | -3(x+4)+2=2(x+5) | | -133+4x=12x+123 | | 7(-2x+2)=4x+50 | | -19-3b=1-b | | 5k+7=11k-25 | | x+76+x+78=180 | | -3x-25=7(x+5) | | 10+x/5–9=√49 | | 3=-12/b | | -80=-7n+4 | | 8=k+1+4 | | 1.2x+3=-0.6x | | 4=15+p | | -8x-4=-3x+9 | | 5(x-7)+6=31 | | 1.4x+5x+5.25=4.25x+3x-7.5 | | 4+-v=10 | | x=-10+4(2) | | 40=d-43 | | -12=-4x+16 | | (⅓)x=81 | | 0.18(y-8)+0.12y=0.04y-3 | | 3(6x-4)-x=2x-6(7-2x) | | -3n+6=-4n-2 | | (3x-1)+4x+2=81 | | 2x+3+4x-12=15 | | 6x-2x+8=x-5+13 | | 3+2(x-5)=-5x | | -6(7+6v)=48 | | 2(u-2)=-6u+12 | | 41^2a-17=4a-11 |

Equations solver categories